Scientific-technical progress and the world crisis (A reading on Edgar Moran’s future philosophy) - ., haba eadil (Al-Adab Journal, 2015)
" Scientific and technical progress and the crisis of the world " Our research aims to shed light on the crisis that the philosopher Edgar Morin discussed . The crisis that occurred as a result of scientific progress gave her , How technical solutions and how kara future based on the results it turned out that the crisis